Analysis of the Effect of Application of E-Commerce, Social Media, and Content Marketing to Increasing Shopping Interest in MSMEs - Putri, Susana Pratiwi; Rafika, Mulya; Limbong, Christine Herawati (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
One of the main advantages of digital marketing is that it allows MSMEs to reach a much larger audience than traditional marketing methods. Implementing digital marketing allows MSMEs to target their ideal customers and communicate with them directly. The purpose of this study was to determine the effect of implementing e-commerce, social media, and content marketing to increase shopping interest in MSMEs. This study uses a quantitative approach that tests numbers and analyzes statistical tests, collects data and uses a sample of 100 respondents to get valid answers. The results of this study show that e-commerce has no significant effect on shopping intentions in MSMEs, social media has no significant effect on shopping intentions in MSMEs, and the last variable, namely content marketing, has proven to have a positive and significant effect on shopping intentions in MSMEs. Researchers see that the application of content marketing greatly influences a consumer's shopping interest. The development of technology is currently very rapid and very influential for people in the business world.